Pengaruh Managerial Ownership Dan Institutional Ownership Terhadap Leverage : Sebuah Tinjauan Teoritis - Christian Herdinata (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2013)
This study aims to examine how the effect of managerial ownership and institutional ownership to leverage the company's policy in Indonesia using research literature review. According to analysis carried out showed that managerial ownership and institutional ownership has an influence on leverage, so the company must pay attention to the influence that mav result from managerial ownership and institutional ownership in the company in lndonesia.